SURVEI BAHAN BAKU KEBUTUHAN PENYEDIA MAKANAN SEBAGAI ACUAN HARGA DASAR DALAM PENGOLAHAN MAKANAN CATERING DI KABUPATEN KUNINGAN - Shifa Atiyatul Hasanah; Kartika; Agung Setiawan (Jurnal Fakultas Teknik Kuningan, 2024)
The catering business is a very promising business. As public awareness of the importance of health and nutrition increases, the demand for catering that serves healthy food and organic raw materials is increasing. Therefore, this research aims to 1) identify the types of raw materials most commonly used in catering, 2) determine the prices of raw materials used in making catering, and 3) determine a reasonable and competitive basic price for catering based on the cost of raw materials used. . This research uses descriptive analysis, the respondents in this research are Mayang Catering, Mak Ijem Catering, and Hana Catering Kuningan